The Practice and Reflections on Ideological and Political Education in Ultrasound Medical Graduate Courses under the “Three-All Education” Perspective - Zhang, Lisu; Chen, Ling; Wang, Xiaodan; Chen, Xinxin; Liu, Xiaolin (Journal of Educational Research and Policies, 2025)
Ultrasound medicine is a discipline that integrates both medical knowledge and technical skills, emphasizing the training of clinically oriented professionals. Under the educational framework of the “Three-All Education” concept, the integration of medical education and ideological-political education has become a growing trend. This study conducted a preliminary analysis of the incorporation of ideological and political education into ultrasound medical graduate courses through a questionnaire survey. The results indicate that most students recognize the importance of ideological and political education and support its integration with professional courses. However, several challenges remain in practice, such as a lack of diverse teaching methods, insufficient time allocation, and limited ideological and political teaching capabilities among some instructors. Based on the survey findings, this study proposes enhancing teachers’ awareness of ideological and political education, improving instructional methods, and leveraging online resources to enrich course content. These measures aim to promote the integration of ideological and political education with ultrasound medical training, fostering high-quality professionals with both technical expertise and a strong sense of social responsibility.